Clinical Outcomes of Condoliase Injection Therapy for Lateral Lumbar Disc Herniation - Yujiro Kagami; Hiroaki Nakashima; Naoki Segi; Ryuichi Shinjo; Shiro Imagama (Spine Surgery and Related Research, 2023)
Introduction: This study aimed to evaluate the efficacy of condoliase injection therapy (CIT) for lateral lumbar disc herniation (LLDH). Methods: This retrospective study included 157 of 180 enrolled patients (70 males, 87 females; mean age: 52.6±16.9 years). These patients were divided into two groups (group L: LLDH, group M: medial LDH [subligamentous and transligamentous]). From baseline to 1 year after injection (final follow-up), leg pain was assessed using the visual analog scale (VAS) and the Japanese Orthopedic Association (JOA) scoring for CIT's clinical efficacy of CIT. Radiography and magnetic resonance imaging conducted before and 3 months after the injection were assessed. Patients with a VAS improvement of 50% at the final follow-up were defined as responders. The responder and nonresponder LLDH groups were also compared. Results: Groups L and M showed comparable responder rates (75.0% and 77.4%, respectively) (P=0.80). VAS and JOA scores at 1 year showed no significant differences between the groups (P=0.82 and 0.80, respectively). VAS score at 1 month after injection reduced considerably in the responder group compared with that in the nonresponder group (19.7 vs. 66.0, P<0.01) and continued to decrease at the last follow-up (3.5 vs. 52.0, P<0.001). Nonresponders had significantly lower disc heights after 3 months. However, intervertebral instability, alignment, and disc degeneration did not differ between the responders and nonresponders. Conclusions: The response rate of CIT for LLDH was comparable to that for medial LDH. Therefore, CIT is an effective treatment for LLDH.